'Rigid‐soft' synergistic effects to improve the microstructure and superflexibility properties of aramid nanofiber aerogel. Issue 42 (24th August 2022) - Li, Jiaoyang; Lu, Zhaoqing; Huang, Jizhen; Hua, Li
Abstract: Designing aramid nanofiber (ANF) aerogel with excellent microstructure and high thermal insulation property is benefit for applications in integrated thermal management system. To obtain a structurally controllable ANF‐based aerogel, the cellulose nanofiber (CNF) and poly (vinyl alcohol) (PVA) were 'stiff–soft' synergistic to improve the microstructure. The cobweb like structures distributed in the honeycomb layered pores of the CNF/PVA/ANF composite aerogel which was conducive to the performance and application of composite aerogel. The resulting CNF1/PVA1/ANF composite aerogels are highly porous (99.12%) and tiny volume shrinkage (4.65%), leading to excellent thermal insulation performance (26.83 mW/m·K). The 'stiff–soft' feature endows the composite aerogels high flexibility as well as large compression strength. These favorable multi‐features make the CNF/PVA/ANF composite aerogels ideal advanced material for aerospace, industrial, and commercial applications. Abstract :